1991
DOI: 10.1111/j.1752-7325.1991.tb02217.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Knowledge and Habits of Senior Elementary School Students

Abstract: Despite improvements in children's dental health, and significant resource allocation to health education programs, few recent studies have investigated the associations of oral health knowledge, behaviors, and status. This study of 11-year-old children (N = 6,329) in northeastern Ontario used a supervised self-complete questionnaire and a clinical examination to gather baseline data on, and test associations of, caries and periodontal knowledge, self-reported oral health behaviors and source of knowledge, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 22 publications
(4 reference statements)
4
55
2
Order By: Relevance
“…Only 6% of the subjects has used dental loss, which is similar to a study conducted by Jamjoom in Saudi Arabia in 2001 [7]. In contrast, Hamilton and Couby [8] found that a high percentage (44%) of the sample they studied in north eastern Ontario used dental loss. Reason for this may be the signi icant resource allocation to health education programs that are carried out in Canada.…”
Section: Discussionsupporting
confidence: 76%
“…Only 6% of the subjects has used dental loss, which is similar to a study conducted by Jamjoom in Saudi Arabia in 2001 [7]. In contrast, Hamilton and Couby [8] found that a high percentage (44%) of the sample they studied in north eastern Ontario used dental loss. Reason for this may be the signi icant resource allocation to health education programs that are carried out in Canada.…”
Section: Discussionsupporting
confidence: 76%
“…For instance, Hamilton and Coulby reported that increase in oral health knowledge was positively correlated with improved behavior and stated that knowledge of health is an important predictor for behavior [4]. The result of Hamilton and Coulby was further confirmed by Ashley [20].…”
Section: Discussionmentioning
confidence: 83%
“…These findings are in agreement with the findings of Daly [19], who reported that positive attitude would lead to improved health behavior. Hamilton and Coulby [4] and Ashley [20] had earlier reported that increase in oral health attitude is positively correlated with improved behavior. Singh et al [22] reported a linear positive relationship oral health attitude and behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Previous Studies have shown that there is a direct relationship between increased knowledge of oral hygiene and better oral health. 11 That mean Oral health knowledge is considered to be an essential prerequisite for health-related behaviour, although only a weak association seems to exist between knowledge and behaviour in crosssectional studies. 9,12 Nevertheless, studies have shown that there is an association between increased knowledge and better oral health.…”
mentioning
confidence: 99%